2020
DOI: 10.1055/a-1124-7225
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy in Breast Cancer

Abstract: In recent years, the blood-based analysis of circulating tumour cells (CTCs) and nucleic acids (DNA/RNA), otherwise known as liquid biopsy, has become increasingly important in breast cancer. Numerous trials have already underscored the high prognostic significance of CTC detection in both early and metastatic stages. Moreover, the changes in CTC levels and circulating tumour DNA (ctDNA) during the course of the disease correlate with the response to treatment. Research currently focuses on liquid-biopsy based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…These omics analyses involve the identification of biomolecules responsible for each step of cell function control from DNA replication (genomics markers) to transcriptional events and posttranscriptional regulation (transcriptomic markers) to protein translation (proteomic markers). These markers can be identified not only in tumor tissues but also by liquid biopsy (Figure 1) [16,17], which could assist in the development of new drugs and in the identification and monitoring of patients who will respond and benefit from this treatment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These omics analyses involve the identification of biomolecules responsible for each step of cell function control from DNA replication (genomics markers) to transcriptional events and posttranscriptional regulation (transcriptomic markers) to protein translation (proteomic markers). These markers can be identified not only in tumor tissues but also by liquid biopsy (Figure 1) [16,17], which could assist in the development of new drugs and in the identification and monitoring of patients who will respond and benefit from this treatment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decades, CTCs have been established as a strong prognostic factor in metastatic breast cancer (MBC) and first studies have shown their potential to guide treatment decisions [2,5,6]. Beyond tumor cellbased analyses, circulating nucleic acids, such as DNA and RNA fragments, can also be routinely detected in peripheral blood [7]. They are released to the bloodstream Oncol Res Treat 2022;45:4-10 DOI: 10.1159/000520561 by primary tumor, metastatic lesions, and decaying CTCs, and detection is usually carried out in blood plasma [7].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond tumor cellbased analyses, circulating nucleic acids, such as DNA and RNA fragments, can also be routinely detected in peripheral blood [7]. They are released to the bloodstream Oncol Res Treat 2022;45:4-10 DOI: 10.1159/000520561 by primary tumor, metastatic lesions, and decaying CTCs, and detection is usually carried out in blood plasma [7]. While the evidence on the prognostic value of circulating tumor DNA (ctDNA) detection in MBC is limited, particularly compared with level I evidence of CTCs, the possibility to detect somatic mutations via liquid biopsy appears promising and the first liquid biopsy-based therapy indication using ctDNA has recently been approved in the USA and European Union [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These past few years, researchers have focused their attention on a new promising diagnostic method, liquid biopsy, which uses biomarkers such as circulating cell tumor, RNA fragments, or cell-free DNA (cfDNA). Unlike tissue samples obtained by invasive methods like needle biopsies or endoscopies, biomarkers can be detected in body fluids, mostly blood[ 4 ], and address limitations of tissues biopsies not only in diagnosis and screening, but also in diagnosis and screening the treatment response and follow-up[ 5 - 7 ]. Among liquid biopsy options, cfDNA raises the most significant hopes in early cancer detection.…”
Section: Introductionmentioning
confidence: 99%